JAEPL, Vol. 11, Winter 2005-2006 - Kristie S. Fleckenstein; Linda T. Calendrillo (Journal of the Assembly for Expanded Perspectives on Learning, 2005)
Essays Kami Day. We Learn More Than Just Writing. In a composition class, students learn a great deal more, for good or ill, than just strategies for writing. This article shows that, as students and teachers learn to recognize and value their own inner teachers, they can also develop relationships with each other that nourish their spirits as well as their intellects. Gina DeBlase. 'I Have a New Understanding': Critical Narrative Inquiry as Transformation in the English-History Classroom. This case study highlights what roles classroom discussion and activity around literature, history, and society play in developing one student’s understanding of complex social issues, and what ways of talking and thinking develop over time. Geraldine DeLuca. Headstands, Writing, and the Rhetoric of Radial Self-Acceptance. By emphasizing the importance of patient practice as an end in itself, yoga offers a model teaching and learning writing that can help students move forward in a context of self-acceptance and find the sources of their own talents and values. Sue Hum. Idioms as Cultural Common Places: Corporeal Lessons from Hokkien Idioms. This essay uses idioms, especially Hokkien idioms, to counter the western predisposition of separating mind and body, arguing that they underscore the mind-body shift that occurs with the acquisition of academic discourses. Laurence Musgrove. What Happens When We Read: Picturing a Reader’s Responsibilities. A graphic representation of reading as a process enables students to respond more fully and responsibly to literature by attending to what they contribute to the act of reading, what the world to the text can offer, what kinds of responses are available to them, and what they can do to make sure they have responded as thoughtfully as possible. Alexandria Peary. Mindfulness, Buddhism, and Rogerian Argument. Use of Buddhist mindfulness practices with Rogerian argument highlights Roger’s ideas of empathy and conscious listening which help develop a rhetorical imagination in the student. Stan Scott. Poetry and the Art of Meditation: Going Behind the Symbols. Combining reader-response theory with spiritual teachings, this article explores how reading poetry may serve as an introduction to the art of meditation. Helen Walker. Connecting. Louise Morgan—Street Science: An English Teacher’s Introduction to Street Life. Amy Wink—'In the Middle of Difficulty Lies Opportunity'— Albert Einstein Marcia Nell—The New Partnership Gergana Vitanova—Negotiating an Identity in Graduate School as a Second Language Speaker. Judy Huddleston—A Cat in the Sun: Reflections on Teaching. Reviews Edward J. Sullivan. Ken Wilber: Thought as Passion. (Frank Visser, 2003). Gabriele Rico. A Way to Move: Rhetorics of Emotion and Composition Studies. (Ed. Dale Jacobs and Laura R. Micciche, 2003). Megan Brown. Living the Narrative Life: Stories as a Tool for Meaning Making. (Gian S. Pagnucci, 2004). Kim McCollum-Clark. Personally Speaking: Experience as Evidence in Academic Discourse. (Candace Spigelman, 2004).